The Policy of Inclusive Education in Indonesia - Novrizal, Nesa; Manaf, Sofwan (Multicultural Islamic Education Review, 2024)
The Policy of Inclusive education plays a crucial role in building an inclusive and equitable society. Quality education obtained by students in general is the same right for children with disabilities. Through Permendiknas No. 70 in 2009, article 1 explains that the education implementation system provides opportunities for all children with disabilities who have the ability and intelligence or have special talents to attend education in an educational environment together with students in general. However, in practice, many schools that organize inclusive education have not fully implemented the policy. This is due to the absence of guidelines for educators in guiding their students. The purpose of this study is to analyze inclusive education policy in Indonesia. This research uses a literature review with documentary techniques as a means of collecting data from trusted sources. The findings of this study are that in implementing inclusive education policies, qualified resources (budget, teaching staff and infrastructure) are needed, interpreting and elaborating policies in the form of regulations to formulate policy implementation, preparing plans for several steps in implementation based on time, place and budget, continuously organizing students, budgets and infrastructure, and providing benefits.